2022
DOI: 10.3389/fphys.2022.829887
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Symbolic Analysis of Heart Rate Variability and Its Changes During Sympathetic Stimulation in Elite Modern Pentathlon Athletes: A Pilot Study

Abstract: Background and PurposeMost studies on heart rate variability (HRV) in professional athletes concerned linear, time-, and frequency-domain indices, and there is lack of studies on non-linear parameters in this group. The study aimed to determine the inter-day reliability, and group-related and individual changes of short-term symbolic dynamics (SymDyn) measures during sympathetic nervous system activity (SNSa) stimulation among elite modern pentathletes.MethodsShort-term electrocardiographic recordings were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
2
2
0
Order By: Relevance
“…A narrowed and shortened shape was obtained in athletes during sympathetic stimulation-this shape was similar to the "torpedo" shape observed in patients with heart failure (77). Our results are in line with previous findings in athletes (34) and healthy adults (43). In the mentioned studies, sympathetic stimulation was induced in modern pentathletes, identical to the present study, by short-term static isometric exercise (34), whereas in adults it was induced by a graded head-up tilt test (43).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A narrowed and shortened shape was obtained in athletes during sympathetic stimulation-this shape was similar to the "torpedo" shape observed in patients with heart failure (77). Our results are in line with previous findings in athletes (34) and healthy adults (43). In the mentioned studies, sympathetic stimulation was induced in modern pentathletes, identical to the present study, by short-term static isometric exercise (34), whereas in adults it was induced by a graded head-up tilt test (43).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous findings in athletes (34) and healthy adults (43). In the mentioned studies, sympathetic stimulation was induced in modern pentathletes, identical to the present study, by short-term static isometric exercise (34), whereas in adults it was induced by a graded head-up tilt test (43). Our findings are similar to those obtained in response to acute mental stress in healthy students (78).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…11,29 A strength of our study is the inclusion of three nonlinear HRV parameters, namely SD2, D2, and DFA1, which have been rarely used in psychophysiological studies although they offer new opportunities to monitor cardiac autonomic control and better reflect physiological processes as they are not linear. 30 Additionally, they offer the advantage of being independent of the mean heart rate and are also suitable for short and nonstationary data series. 26,31 In our study, participants with MCI showed significantly lower values compared to HCs, indicating lower heart rate complexity in MCI participants.…”
Section: Discussionmentioning
confidence: 99%